Jurnal: Perancangan Desain Karakter Pendukung dalam Kampanye Gizi Pada Anak Usia 3 - 5 Tahun - Puspita, Shinta Rahma; Wulandari, Sri; Aqidatun Nisa, Diana (Innovative: Journal Of Social Science Research, 2024)
This journal discusses the design of supporting characters in a nutrition campaign for children aged 3-5 years. With the background of the need for a creative approach in children's nutrition education, this journal explains the roles and benefits of supporting characters such as Captain Carrot, BroCollin, Milkkuat, and Professor Pisang in providing support, education, and motivation to children. It is hoped that these character designs can enhance early childhood nutrition awareness in a fun and effective way.